Proteorhodopsin-Like Genes Present in Thermoacidophilic High-Mountain Microbial Communities - Bohorquez, Laura C. (American Society for Microbiology, 2012)
Proteorhodopsin (PR) sequences were PCR amplified from three Andean acidic hot spring samples. These sequences were similar to freshwater and marine PRs and they contained residues indicative of proton-pumping activity and of proteins that absorb green light; these findings suggest that PRs might contribute to cellular metabolism in these habitats.